Differences of dynamic responses of single-pile and pile-group foundations in Meizoseismal areas - Yunxiu Dong; Zhongju Feng; Jingbin He; Zhen Wang; Bo Wang (PLoS ONE, 2026)
In order to investigate the dynamic response variations between isolated pile and pile-group systems in high-seismicity regions, we performed extensive shaking table experiments. These tests examined the acceleration characteristics, displacement patterns, and bending moment distributions across single-pile, four-pile, and six-pile configurations when exposed to four different seismic waveforms at a design-level intensity of 0.35g. Additionally, the structural integrity and damage conditions of the pile foundations were systematically assessed. The experimental data revealed that the greatest displacement at the pile head and the highest bending moment values were specifically caused by Kobe wave excitation. Conversely, the El-Centro wave produced the highest acceleration amplifications. The six-pile foundation exhibited optimal resistance to displacement and bending moment, particularly under the 5010 wave, and the single-pile foundation consistently showed the least acceleration amplification. Post-test inspections, including white-noise scanning and visual checks, showed no evidence of significant macroscopic damage across all foundation types, indicating an essentially elastic response at this intensity level. Engineering suggestions for the seismic design of bridge pile foundations in strong earthquake areas are proposed.